The Development of Four-Tier Diagnostic Test Instrument to Identify the Learners’ Misconception on Circular Motions - Wahyuni, Nina; Bhakti, Yoga Budi; Mutakin, Tatan Zenal; Astuti, Irnin Agustina Dwi (Impulse: Journal of Research and Innovation in Physics Education, 2021)
Difficulty understanding students' concepts needs to be known so that improvements can be made so that eventually students can master the concepts well. Misconception diagnostic tests can be an alternative to uncovering causes or factors of misconception in students. This study aims to develop a Four-Tier Test diagnostic test instrument to diagnose students' misconceptions on circular motion material. This research is a development study using 4D models. The developed four-tier test diagnostic test instrument consists of 40 multiple-choice questions. The results of the content validation by five experts stated that the instrument was very feasible with an average percentage of 86,34%. Empirical trial results show as many as 40 valid diagnostic test items have enough to good power a level of difficulty and discrimination power. The reliability of the questions was analyzed using the Kuder Richardson formula of 0.785 with a high category. This instrument can be used to minimize the time spent in the process of identifying misconceptions because it is in the form of multiple-choice with varied questions.